THE WORLDWIDE SETTING OF HIGHER EDUCATION QUALITY ENHANCEMENT ACTIVITIES COUPLED WITH KPIS: AN OPEN COMPOSITION FOR YARMOUK UNIVERSITY IN JORDAN - Ali A. A. Rawabdeh; Rami M. Tubaishat (Proceedings on Engineering Sciences, 2019)
The Higher Education within the glob presently a day confront an unused time due to changes within the way individuals see higher education educate. They have achieved numerous add-up to quality profile in terms of quantity and quality at programs and graduate levels in the world. Desires for ways better execution in terms of instructing and creating competent college graduates are expanding. In the meantime, universities strike to expand certain avances at the international level in terms of expanding vertically and horizontally to offer a solid high quality and progressed learning opportunities to satisfy client needs. To achieve this, higher education arrangements higher education policy makers ought to make such an environment in which agencieshas pride in their work and keep up with new developments and changes.